Active and Passive Maternal Smoking During Pregnancy and Birth Outcomes: A Study From a Developing Country - Shereen Hamadneh; Jehan Hamadneh (Ubiquity Press, 2021)
Background: Smoking is one of the modifiable risk factors for adverse maternal and neonatal outcomes and is associated with low birth weight, preterm birth, respiratory, antepartum and intrapartum stillbirth, and perinatal death as well as long-term morbidity in offspring and sudden unexpected infant death. The rate of smoking in low- and middle-income countries is still relevantly high, and Jordan is no exception. Objective: To investigate the effect of active and passive smoking during pregnancy on adverse pregnancy outcomes. Methods: The case-control study was conducted in Jordan in June 2020. Healthy women with full-term singleton pregnancy (n = 180) were interviewed and stratified into three groups: Group I, active smokers; Group II, passive smokers; and Group III, nonsmokers. The study variables included demographic data, current pregnancy history, cotinine level of mothers and newborns, and perinatal outcomes. Statistical analysis was performed using the application package IBM SPSS 25. Various algorithms of statistical analysis were used depending on the type of distribution of feature and data quality. The threshold for statistical significance was set at 'p' < 0.05. Results: Active smokers had significantly lower gestational age at delivery compared to passive and nonsmoking women ('p' = 0.038 and 'p' = 0.003, respectively). Neonates from active smoking mothers had significantly lower birth weight compared to neonates from passive and nonsmoking women ('p' = 0.016 and 'p' = 0.019, respectively), significantly lower head and chest circumferences compared to babies from passive smokers ('p' < 0.001 and 'p' = 0.036, respectively), and significantly lower first-minute Apgar score compared to those from nonsmoking women ('p' = 0.023). The urine cotinine level was significantly higher in both active and passive smoking women (both 'p' < 0.01), and it was significantly higher in newborns who had been exposed to smoking in utero despite maternal active or passive smoking status (both 'p' < 0.001). There was a weak negative correlation between urine cotinine level and birth weight: 'r' = -0.14 for maternal cotinine level and 'r' = -0.15 for neonate cotinine level. Conclusions: The current study illustrated that smoking during pregnancy leads to offspring with reduced birth weight, birth length, and head and chest circumference; reduces delivery gestational age; and lowers the first-minute Apgar score. Our study findings highlight the need for further research issued to smoking effects on perinatal outcomes, the implementation of actions to develop cessation interventions in the preconception period, and an evaluation of useful interventions to enhance a smoking-free environment during pregnancy.